Comparison of strategies for enhancing RNA interference efficiency in Ostrinia nubilalis. Issue 2 (19th October 2020) - Cooper, Anastasia MW; Song, Huifang; Yu, Zhitao; Biondi, Marie; Bai, Jun; Shi, Xuekai; Ren, Zhaoyang; Weerasekara, Sahani M; Hua, Duy H; Silver, Kristopher; Zhang, Jianzhen; Zhu, Kun Yan
Abstract: BACKGROUND: Targeting insect‐specific genes through post‐transcriptional gene silencing with RNA interference (RNAi) is a new strategy for insect pest management. However, lepidopterans are recalcitrant to RNAi, which prevents application of novel RNAi technology to many notorious pests, including Ostrinia nubilalis (ECB). Strategies for enhancing RNAi efficiency, including large doses of double‐stranded RNA (dsRNA), nuclease inhibitors, transfection reagents, and nanoparticles, have proved useful in other insects exhibiting substantial dsRNA degradation, a major mechanism limiting RNAi efficacy. To determine if similar strategies can enhance RNAi efficiency in ECB, various reagents were tested for their ability to enhance dsRNA stability in ECB tissues, then compared for their effectiveness in whole ECB. RESULTS: Ex vivo incubation experiments revealed that Meta dsRNA lipoplexes, EDTA, chitosan‐based dsRNA nanoparticles, and Zn 2+ enhanced dsRNA stability in ECB hemolymph and gut content extracts, compared with uncoated dsRNA. Despite these positive results, the reagents used in this study were ineffective at enhancing RNAi efficiency in ECB in vivo . To reduce assay time and required dsRNA, midguts were dissected and incubated in tissue culture medium containing dsRNA with and without reagents. These experiments showed that RNAi efficiency varied between target genes, and nuclease inhibitors improved RNAi efficiency for only a portion of the refractory target genes investigated ex vivo . CONCLUSION: These results indicate that enhancing dsRNA stability is insufficient to improve RNAi efficiency in ECB and suggests the existence of additional, complex mechanisms contributing to low RNAi efficiency in ECB. Abstract : This research article investigates putative RNAi‐efficiency enhancing reagents for their ability to enhance dsRNA stability and/or RNAi efficiency in multiple life stages of the European corn borer. © 2020 Society of Chemical Industry